Primulina purpurea F. Wen, B. Zhao & Y.G Wei (Gesneriaceae), a new species from China (Bangladesh Journal of Plant Taxonomy, 2012)
Primulina purpurea F. Wen, B. Zhao & Y.G Wei, a new species from East Guangxi, China, is described and illustrated. The new species resembles P. medica (D. Fang) Y. Z. Wang, but differs from the latter by having broadly ovate to elliptic, left-right slightly asymmetry leaf blade, brightly purple to fuchsia corolla, broadly lanceolate to narrowly ovate bracts with villous hairs outside and pubescent hairs inner, pistil 23.526.8 mm long, staminodes 3, capsule 4.5-5.0 cm long. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13131 Bangladesh J. Plant Taxon. 19(2): 167-172, 2012 (December)